Assessment of Municipal Solid Waste Clay Liner System Using Consolidation Test - G. Venkatesan; G. Swaminathan (The Global Environmental Engineers, 2015)
The present study has been carried out to provide landfill clay liner soil with admixture microsilica in different proportions. The geoenvironmental and physico-chemical characteristics were carried out to characterize the clay mixed with definite portion of microsilica in mass ratio. An experimental investigation was performed to determine the effect of clay and microsilica consolidation of leachate. The microsilica- clay composites were mixed in ratios of 0:100, 1:10 and 1:20 and experiment carried out with leachate as the permeation liquid. The quantitative reductions in coefficient of permeability increase in the effective stress for the all ratios. The chemical reaction of water and soil are lower than that in the leachate. In real field the leachate as permeation liquid after construction of liners, is retained by adding microsilica in clay liner system. 1:10 ratio of microsilica-clay composites was found to be more suitable municipal solid waste leachate as permeating liquid.